Reassessing Mangrove Community Structure in Ekas Buana, Indonesia: An Ecological Baseline for Low-Impact Tourism Planning - Muhammad Aminuddin (Tinta Emas Publisher, 2026)
Mangrove tourism can create conservation finance, local employment, and environmental-learning opportunities, but visitor access and poorly located infrastructure may also damage roots, regeneration, sediment, and tidal connectivity. This study provides a transparent ecological baseline for low-impact tourism planning in Ekas Buana, East Lombok, Indonesia. It is a secondary reassessment of a field survey conducted at five stations from October to December 2018 and published in 2019; no new field measurements or tourism surveys were collected. Stage-specific importance value indices (IVI) were reconstructed from the published figures, while Shannon diversity, Pielou evenness, and Simpson diversity were recalculated from published relative-density proportions. Six mangrove species were recorded across all stages. Sonneratia alba dominated the tree layer (IVI 114.40%), whereas Rhizophora apiculata dominated saplings (84.31%) and seedlings (91.10%). Recalculated Shannon diversity was 1.481 for trees, 1.558 for saplings, and 1.234 for seedlings; evenness was 0.920, 0.968, and 0.890, respectively. The source survey reported sandy to sandy-mud substrate, salinity of 4.1–5.2‰, temperature of 29–31°C, and pH of 7.40–7.53. The shift in dominance among life stages supports differentiated spatial protection for mature stands and regeneration areas, but it does not establish temporal recovery or decline. We translate the baseline into a precautionary three-part planning logic: no-build conservation areas, a field-validated guided interpretation corridor, and landward visitor-service areas. Because plot-level, hydrological, visitor-flow, livelihood, and governance data are unavailable, the study does not claim present condition, tourism suitability, or carrying capacity. A renewed ecological and social baseline is therefore a prerequisite for infrastructure investment.